Platelet Surface Protein Expression and Reactivity upon TRAP Stimulation after BNT162b2 Vaccination - Klug, Melissa; Lazareva, Olga; Kirmes, Kilian; Rosenbaum, Marc; Lukas, Marina; Weidlich, Simon; Spinner, Christoph D.; Von Scheidt, Moritz; Gosetti, Rosanna; Baumbach, Jan; Ruland, Juergen; Condorelli, Gianluigi; et al. (Thrombosis and Haemostasis, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection induces a coagulopathy characterized by platelet activation and a hypercoagulable state with an increased incidence of cardiovascular events. The viral spike protein S has been reported to enhance thrombosis formation, stimulate platelets to release procoagulant factors, and promote the formation of platelet-leukocyte aggregates even in absence of the virus. Although SARS-CoV-2 vaccines induce spike protein overexpression to trigger SARS-CoV-2-specific immune protection, thrombocyte activity has not been investigated in this context. Here, we provide the first phenotypic platelet characterization of healthy human subjects undergoing BNT162b2 vaccination. Using mass cytometry, we analyzed the expression of constitutive transmembrane receptors, adhesion proteins, and platelet activation markers in 12 healthy donors before and at five different time points within 4 weeks after the first BNT162b2 administration. We measured platelet reactivity by stimulating thrombocyte activation with thrombin receptor-activating peptide. Activation marker expression (P-selectin, LAMP-3, LAMP-1, CD40L, and PAC-1) did not change after vaccination. All investigated constitutive transmembrane proteins showed similar expressions over time. Platelet reactivity was not altered after BNT162b2 administration. Activation marker expression was significantly lower compared with an independent cohort of mild symptomatic COVID-19 patients analyzed with the same platform. This study reveals that BNT162b2 administration does not alter platelet protein expression and reactivity.
CRIS-Team Scopus Importer:2023-03-08
Keywords: COVID-19; platelet activation; platelets; SARS-CoV-2 vaccines